Multifunctional agriculture: An engine of regional economic growth? - Randall, Alan (Applied Studies in Agribusiness and Commerce, 2010)
The historical role of agriculture in economic geography and recent conceptual developments – including multifunctional agriculture (MFA), the new economic geography, amenity-driven growth, and the “world is flat” and “creative class” hypotheses – are examined, and recent empirical research in NorthAmerica and Europe is reviewed, in order to assess the potential for MFA as an engine of regional economic growth. Ideal MFA policy corrects market failures and is mostly amenity-augmenting. It has the capacity to enhance opportunities for farmers on urban fringe; stimulate growth in high-amenity rural regions accessible to cities that offer opportunities for high-value work; and generate growth in relatively remote high-amenity regions. The scope for market-failure-correcting MFA policy to propel economic growth in lessfavored regions is limited – remoteness is non-responsive to policy in the short to medium term, and amenities that attract in-migration (e.g. proximity to sea, lakes, mountains, pleasant climate) are givens for favored locations but can at best be complemented by pro-active policy – but not trivial. While this paper focuses on regional economic growth, it well to rememberthat growth is not everything. Regions unlikely to experience growth need to create satisfying futures. Market-failure-correcting MFA policy has the potential to improve quality of life, well-being, and perhaps incomes in many if not all rural places regardless of location. This accomplishment would not be trivial – economic growth for all regions regardless of resources, amenities, and remoteness is not a serious prospect, and regions in decline face daunting problems maintaining essential services and quality of life.